9=3x-6(x+3)

Simple and best practice solution for 9=3x-6(x+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9=3x-6(x+3) equation:



9=3x-6(x+3)
We move all terms to the left:
9-(3x-6(x+3))=0
We calculate terms in parentheses: -(3x-6(x+3)), so:
3x-6(x+3)
We multiply parentheses
3x-6x-18
We add all the numbers together, and all the variables
-3x-18
Back to the equation:
-(-3x-18)
We get rid of parentheses
3x+18+9=0
We add all the numbers together, and all the variables
3x+27=0
We move all terms containing x to the left, all other terms to the right
3x=-27
x=-27/3
x=-9

See similar equations:

| 9=3x-6(x=+3) | | 8+6x-16=2x+4 | | 15x=6x+8 | | 3y+5y10y-4y=0 | | –6+5t=5t−3 | | 30y-10y+20y+500=120-20 | | |2-x|=|3x+2| | | |6x|=12 | | 3x(4+)x=36 | | 1/7w=12 | | 2y-y+5y=18 | | 6−2t=–3t | | 2/3c-4+2=3/2c+3 | | H(x)=-3/4x-1 | | 11r-3=118 | | -5x-6(2x+4)=129 | | h(11)=−20+11 | | 3x-2)=13x-92 | | (5x+4)/(2x-7)=0 | | 40p+50=50p+60 | | 2/3c-4+2=3/2c=3 | | 3(x+2)-4=(x-1)+5 | | 9x-9x=0x | | 12+8q=15=7q | | 5/1=x/10 | | -2b+6b+2-2b=8+5b | | −9x=14 | | 125=5x2 | | 40-4x/3=2+0.25x | | 4/10+5/10=y/5 | | 2x+21=-6+3x | | (314)+10=5.6p-96 |

Equations solver categories